Chromosomal-Level Assembly of the Asian Seabass Genome Using Long Sequence Reads and Multi-layered Scaffolding. - Shubha Vij; Heiner Kuhl; Inna S Kuznetsova; Aleksey Komissarov; Andrey A Yurchenko; Peter Van Heusden; Siddharth Singh; Natascha M Thevasagayam; Sai Rama Sridatta Prakki; Kathiresan Purushothaman; Jolly M Saju; Junhui Jiang; et al. (PLoS Genetics, 2016)
We report here the ~670 Mb genome assembly of the Asian seabass (Lates calcarifer), a tropical marine teleost. We used long-read sequencing augmented by transcriptomics, optical and genetic mapping along with shared synteny from closely related fish species to derive a chromosome-level assembly with a contig N50 size over 1 Mb and scaffold N50 size over 25 Mb that span ~90% of the genome. The population structure of L. calcarifer species complex was analyzed by re-sequencing 61 individuals representing various regions across the species' native range. SNP analyses identified high levels of genetic diversity and confirmed earlier indications of a population stratification comprising three clades with signs of admixture apparent in the South-East Asian population. The quality of the Asian seabass genome assembly far exceeds that of any other fish species, and will serve as a new standard for fish genomics.